BANKING SECTORS IN EMU - CLUSTER ANALYSIS - Knotek, Pavel (European Scientific Journal, ESJ, 2014)
European monetary union (EMU) has been already in the second decade of its existence. We observe that the euro area is heterogeneous and few imbalances occurred during previous years. The most discussed imbalances are connected with different macroeconomic development of member countries and divergent participation in trade and capital flows. The different economic development should be reflected also in banking sectors of individual member countries. Gradual adopting of euro led to creation of one big European bank market which uses in transactions one currency euro, but still we can find a lot of differences between individual banking systems of member countries which are also results of previous development. A lot of new regulation has been prepared and implemented for all banks in euro area after 2008, moreover in connection with banking union project. The main aim of this paper is to deal with individual banking sectors across euro area - find out if banking sectors are similar and to find possible clusters among them.